Analisis Efektivitas Praktikum Cookbook Laboratorium dan Inquiry Laboratory dalam Meningkatkan Keterampilan Siswa Abad 21 - Widayana, Sela Putri; Malik, Adam (Universitas Garut, 2024)
Practicum is an essential component of science education, particularly in fostering 21st-century skills such as critical thinking, communication, collaboration, and problem-solving. This study aims to analyze the effectiveness of two laboratory practicum models, namely cookbook and inquiry, in enhancing these skills. A literature review approach was employed, analyzing 11 journals and 3 textbooks. The results show that cookbook practicum is more effective in improving critical thinking (n-gain = 0.72) and problem-solving skills (n-gain = 0.68) due to its structured and systematic approach. Conversely, inquiry practicum excels in enhancing collaboration (n-gain = 0.78) and communication skills (n-gain = 0.76) as it emphasizes independent exploration and teamwork. The combination of both models provides a more holistic improvement, with an average n-gain of 0.65 across all skills. This study recommends the combined use of cookbook and inquiry practicums to optimally develop 21st-century skills. These findings are expected to serve as a reference for educators in designing science learning strategies that align with global demands.